If it's not what You are looking for type in the equation solver your own equation and let us solve it.
12(p-4)=(6p+10)
We move all terms to the left:
12(p-4)-((6p+10))=0
We multiply parentheses
12p-((6p+10))-48=0
We calculate terms in parentheses: -((6p+10)), so:We get rid of parentheses
(6p+10)
We get rid of parentheses
6p+10
Back to the equation:
-(6p+10)
12p-6p-10-48=0
We add all the numbers together, and all the variables
6p-58=0
We move all terms containing p to the left, all other terms to the right
6p=58
p=58/6
p=9+2/3
| 3(x+9)^=54 | | 8/x=24/15 | | 18x+63=4x+14 | | 5a/2=2a+5 | | 0.2-1/x^2=0 | | 3x²+4×−2=0 | | 3(2x+4)=9x+9-3x+3 | | 9+6x=8x-13 | | 7v/10+2=5v/6 | | (x-3)⋅(x+2)=2x-6 | | (y+3)(3y-6)=0 | | x^-2-72=0 | | 2c+8=|10c| | | (y=3)(3y-6)=0 | | (x-3)⋅(x+2)-(2x-6)=0 | | 8y+4=2y-2 | | x-4/12=3/2 | | 3+x√2=-√2 | | -4(b+8)=-1+3(-b-5) | | 2m^2-2m-1.5=0 | | 3(w-1)=w+1-2(-7w-6) | | 1/x^2=0.2 | | 4/5y=1/6 | | -8(4+9x)=7(-2-11x | | x+3=x*1.25 | | 3(9q-)=9q-27 | | 11/7x+49-2/x+7=5/7 | | 2(u-3)-4u=-4 | | 3+x✓2=-✓2 | | y/4+1=3 | | 3(n-8)+6(n-19)=6 | | -3(v-2)=8(v-6)-2v |